Decision Making in Financial Strategies from Small Business - M.C. Grecia Itzel Tirado Gálvez; Claudia Lizbeth Tirado Gálvez; Marcela Rebeca Contreras Loera (International Journal of Small and Medium Enterprises and Business Sustainability, 2015)
The role of small and medium enterprises (SMEs) worldwide is considered key because of its considerable input with regard to the production and distribution of tangible and intangible assets; at the same time, they are considered flexible because they have rapid adaptation to technological change and potential to create jobs. In this regard, SMEs give the means to promote economic development and competitiveness of any locality. In this context, it is clear the importance of SMEs internationally. Therefore, the objective of this study is to analyze the decision-making on financial strategies from small business. The research was conducted under the qualitative methodological perspective, by focusing on analysis of primary data collected through interviews and observation, and secondary information obtained through books, scientific articles and newsletters produced by federal and state organizations in Mexico. This research is preliminary only and it will serve as a preparation for future detailed study. The findings indicate that financial strategies proposed by the owner of the small business does not embody the necessary elements to achieve them properly, and that even when written goals are set, these have not given a real track, but only remain in paper without proper follow up or incentives for sellers to be motivated to reach sales levels that should be achieved to address the planned expenditures. In this regard it is noted how the process of decision making is not followed in a proper way because it lacks a real analysis of alternatives and on the other hand it its seen that the financial strategy is left embodied without follow up, because of this motive the established goals are not reached.